Difference Test of Formal Compliance and Material Compliance in PBB-P2 Payment by Taxpayers in Bondowoso Regency - Nova Rofikah; Diyah Probowulan; Achmad Syahfrudin Zulkarnnaeni (Westscience Press, 2024)
Compliance in paying taxes is indispensable. Taxpayer compliance is an obligation or act of compliance in its obligation to pay taxes where taxpayers must fulfill all their tax obligations and rights. Compliance itself is divided into 2 parts, namely formal compliance and material compliance. The purpose of this study was to determine and analyze whether there is a difference between formal compliance and material compliance in PBB-2 payments in Bondowoso District. The research method used in this study is comparative research with a quantitative approach. This study will compare whether or not there is a difference between formal compliance and material compliance in Bondowoso District. This study used a sample of 3544 respondents who were taxpayers in Bondowoso Regency. This study used purposive sampling and used technical data analysis Normality Test, Homogeneity Test, Independent t-test (Mann-Whitney Test), testing was carried out using the SPSS Software program (Statistical Package For The Social Sciences) Version 21. The results of this study show that there is no difference between formal compliance and material compliance in PBB-P2 payments in Bondowoso District.